Experimental research of dynamic vibration damping for rigid busbar structures - Fomenko Serafim; Garanzha Igor; Tanasoglo Anton (E3S Web of Conferences, 2023)
Introduction: in the case when flexible structures interact with the wind flow, various phenomena of aerodynamic instability may arise. Typical representatives of such phenomena are vortex wind excitation of cylindrical structures, galloping of poorly streamlined structures with a square, rectangular or rhomboid cross-section, etc. The article highlights some basic ways of damping vibrations of rigid busbar structures. Materials and methods: the method of dynamic vibration damping consists in attaching additional devices to the vibration protection object to change its vibration state. The work of dynamic dampers is based on the formation of force effects transmitted to the object. It differs from another method of vibration reduction, characterized by the imposition of additional kinematic connections on the object such as fixing its particular points. Results: a mathematical model of the plate dynamic damper operation with a point load is presented. To determine the optimal parameters of dynamic vibration dampers, their calculation was performed, taking into account the joint action of the rigid busbar and the damper. Experimental research of the conjoint work of a rigid busbar with a plate dynamic damper is carried out. Conclusions: the effective application of plate dynamic dampers with a point load has been confirmed both outside and inside the tube busbar. Is proposed the special plate vibration damper. This allows to increase the logarithmic decrement of oscillations by 3-3.5 times and reduce the amplitude of oscillations of rigid busbar structures in the resonant mode by 12 time.